Pengaruh Media Audio Visual Terhadap Hasil Belajar Peserta Didik pada Materi Siklus Air di Kelas V SD Negeri 1 Calang Kabupaten Aceh Jaya - Nova Refina; Alfiati Syafrina; Linda Vitoria (Universitas Syiah Kuala, 2023)
In learning science it requires a concept discovery process in understanding the lesson, such as using learning media. During observations in class V SD Negeri 1 Calang the teacher found that the teacher only used pictures in the book on the water cycle material. This study aims to see the effect of audio-visual media on student learning outcomes on the water cycle material. The approach used is a quantitative and experimental approach, namely the type of research with a one group pretest and posttest design model. The place where this research was carried out was at SD Negeri 1 Calang on Jalan Attorney No. 10, Happy Village, Krueng Sabee District, Aceh Jaya Regency. The population for this study were all students of class V SD Negeri 1 Calang, Aceh Jaya Regency, amounting to 21 people because the population was not enough 30, therefore the entire population was sampled. The data collection technique used a pretest and posttest made of multiple choices. SPSS statistics version 25 is the data analysis technique used. To prove the hypothesis used is a paired sample test t test which obtained a significance value (2-tailed) of 0.000 0.05. The results of the criteria for these values are H₀ rejected and Ha accepted, so it can be concluded that there is a significant effect audio-visual media on student learning outcomes on the water cycle material in class V SD Negeri 1 Calang, Aceh Jaya Regency.